PENERAPAN MODEL COOPERATIVE LEARNINGTIPE STAD DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA TENTANG BANGUN DATAR PADA SISWA KELAS III SD - Mukti, Anggun Fandi (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: Application cooperative learning model type stad in enchancing of mathematics learning abaut two dimentional figure in the third grade studentsstate elementary school 1 kretek academic year 2013/2014.The objective of this research is to improve mathematics learning abaut two dimentional figure in the third grade students of SD Negeri 1 Kretek in academic year of 2013/2014.This research is conducted within three cycles consisted of planning, action, observation, and reflection. Subjects of the research were 37 students of the third grade of SD Negeri 1 Kretek. Sources of data were derived students and document. Techniques of collecting data were test, observation, interview, and documentation. Data were analyzed using quantitative and qualitative descriptiveanalysis. It was proven by the increase of learning process in the first cycle 69%, in the second cycle 79,5%, and in the third cycle 90,5%. The results showed that through the implementation of cooperative learning model type STAD can improve learning mathematics abaut up flat in third grade students Elementary School. Keywords: STAD, learning up flat Abstrak:Penerapan Model Cooperative learning Tipe STAD dalam Peningkatan Pembelajaran Matematika Tentang Bangun Datar pada siswa Kelas III Sekolah Dasar. Penelitian ini bertujuan untukmeningkatkan hasil belajar pada pembelajaran matematika tentang bangun datar di kelas III SDN 1 Kretek tahun ajaran 2013/2014.Penelitian dilaksanakan tiga siklus, tiap siklus terdiri atas perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas III SD Negeri I Kretek dengan 37 siswa. Sumber data berasal dari dokumen dan siswa. Teknik pengumpulan data adalah dengan tes, observasi, wawancara, dan dokumentasi. Analisis data yang digunakan dengan analisis kualitatif dan kuantitatif. Persentase ketuntasan siswa sebelum tindakan adalah 54%, setelah dilaksanakan tindakan siklus I meningkat menjadi 69%, siklus II meningkat menjadi 79,5% dan siklus III meningkat kembali menjadi 90,5%. Hasilnya menunjukkan bahwa Penerapan Model Cooperative Learning tipe STADdapat meningkatkan pembelajaran Matematika tentang bangun datar pada siswa kelas III sekolah dasar. Kata kunci: STAD, pembelajaran bangun datar